Pending challenges for dissemination in the field of inclusive university education in Chile - Mellado López, Héctor; Jiménez Poblete, María Paz; Flores Alarcón, Tania (Re-presentaciones: Periodismo, comunicación y sociedad, 2022)
The purpose of this article is to show an experience of the Faculty of Health Sciences of the Universidad de Atacama in which strategies were proposed to reduce the learning barriers faced by students with disabilities. From a methodological work based on the principle of action research, both the production of knowledge and the promotion of changes in practice related to inclusive culture were worked simultaneously. Specifically, different methods of information production and transformation were used, including surveys and interviews. The results showed that academics have a deficient preparation in inclusive education issues, and that they do not have access to timely and current information on this subject at the institutional level. The importance of access to accurate scientific information by the community and the role of knowledge dissemination in this scenario are discussed.
Keywords: learning barriers; dissemination; disability; inclusive culture